Serotonergic Modulation of Nigrostriatal and Mesolimbic Dopamine and Motor/Exploratory Behaviors in the Rat - Nikolaus, Susanne; Wittsack, Hans-Jörg; Antke, Christina; Beu, Markus; Hautzel, Hubertus; Decheva, Cvetana; Mamlins, Eduards; Mori, Yuriko; Huston, Joseph P.; Antoch, Gerald; Müller, Hans-Wilhelm (Frontiers in Neuroscience, 2021)
Purpose: The 5-HT2A receptor (R) is known to modulate dopamine (DA) release in the mammalian brain. Altanserin (ALT) and 2,5-dimethoxy-4-iodoamphetamine (DOI) act as 5-HT2AR antagonist and agonist, respectively. In the present study, we assessed the effects of ALT and DOI on motor and exploratory behaviors and on D2/3R binding in the rat brain with in vivo imaging methods. Methods: D2/3R binding was determined after systemic application of ALT (10 mg/kg) or DOI (0.5 mg/kg) and the respective vehicles (dimethyl sulfoxide [DMSO] and 0.9% saline [SAL]) with [123I]IBZM as SPECT radioligand. Anatomical information for the delineation of the target regions was obtained with dedicated small animal MRI. Immediately after 5-HT2AR antagonistic or agonistic treatment, motor/exploratory behaviors were assessed for 45 (ALT) or 30 min (DOI) in an open field. Additional rats underwent behavioral measurements after injection of DMSO or SAL. Results: ALT increased D2/3R binding in the ventral hippocampus relative to vehicle, while DOI augmented D2/3R binding in caudateputamen, frontal cortex, motor cortex and ventral hippocampus. The 5-HT2AR agonist as well as antagonist decreased parameters of motor activity and active exploration. However, ALT, in contrast to DOI, decreased explorative head-shoulder motility and increased sitting. Conclusions: The regional increases of D2/3R binding after ALT and DOI (90 and 75 min post-challenge) may be conceived to reflect decreases of synaptic DA. The reductions of motor/exploratory activities (min 1-45 and min 1-30 after challenge with ALT and DOI, respectively) contrast the regional reductions of D2/3R binding, as they indicate elevated DA levels at the time of behavioral measurements. It may be concluded that ALT and DOI modulate DA in the individual regions of the nigrostriatal and mesolimbocortical pathways differentially and in a time-dependent fashion.